Предмет: Математика,
автор: Аноним
1,2-2*(1,3х+1)=5,6х-27,04
Ответы
Автор ответа:
5
1,2-2*(1,3х+1)=5,6х-27,04
1,2-2,6x-2=5,6x-27,04
-0,8-2,6x=5,6x-27,04
5,6x+2,6x=27,04-0,8
8,2x=26,24
x=26,24:8,2
x=3,2
1,2-2,6x-2=5,6x-27,04
-0,8-2,6x=5,6x-27,04
5,6x+2,6x=27,04-0,8
8,2x=26,24
x=26,24:8,2
x=3,2
Автор ответа:
1
1,2-2*(1,3х+1)=5,6х-27,04
1,2-2,6x-2=5,6x-27,04
-0,8-2,6x=5,6x-27,04
5,6x+2,6x=27,04-0,8
8,2x=26,24
x=3,2
1,2-2,6x-2=5,6x-27,04
-0,8-2,6x=5,6x-27,04
5,6x+2,6x=27,04-0,8
8,2x=26,24
x=3,2
Похожие вопросы
Предмет: Другие предметы,
автор: Pozitiv44rus
Предмет: Русский язык,
автор: marinavasileva12
Предмет: Окружающий мир,
автор: selezneva2007
Предмет: Математика,
автор: soda93
Предмет: Алгебра,
автор: selfish2042